"Nails Only" Phenotype and Partial Dominance of p.Glu170Lys Mutation in a Family with Epidermolysis Bullosa Simplex. Issue 4 (19th April 2017) - González‐Cantero, Álvaro; Sánchez‐Moya, Ana Isabel; Pérez‐Hortet, Cristina; Martínez‐Lorenzo, Elena; Gómez‐Dorado, Blas; Schoendorff‐Ortega, Cristina
Abstract: Epidermolysis bullosa (EB) is a heterogeneous group of rare, chronic, inherited skin disorders characterized by marked mechanical fragility of epithelial tissues, with blistering and erosions after minor trauma. We present the first report of a nails‐only phenotype in two patients with epidermolysis bullosa simplex (EBS) and a heterozygous pGlu170Lys mutation and the second reported case of EBS associated with a homozygous p.Glu170Lys mutation in the KRT5 gene. Our findings may be relevant for genetic counseling and for understanding the inheritance pattern of EBS.